Climate information services need assessment and inventory of CIS dissemination platforms to scale up access to relevant CIS by farmers and pastoralists in Senegal - Ouédraogo, Issa; Girvetz, Evan Hartunian; Loboguerrero Rodriguez, Ana María (CGIAR System Organization, 2022)
In Senegal, the use of climate information services (CIS) to inform decision-making in the farming system during the growing seasons has increased since 2016. Dedicated dissemination channels have been developed to timely communicate CIS to farmers. In 2022, in the bid to improve the productivity of irrigated agriculture during the dry seasons and to build the resilience of pastoralists, the assessment of CIS need (for irrigation and livestock production) and inventory and evaluation of existing dissemination platforms were done through stakeholder consultation meetings and interviews of key informants. From these meetings, four CIS including off-season rain, temperature, wind and sandstorm forecasts are needed to guide the decision-making for irrigation farming and a long list of 15 CIS is made for pastoralism. SMS (text), Interactive Voice Response (IVR), community radios and social media (Facebook and WhatsApp, mainly) were identified as potential dissemination platforms for both farming and livestock activities. In addition, seven multidisciplinary working groups (MWG) were selected to be capacitated to translate CIS into actionable advisories.